2018
DOI: 10.1016/j.pubrev.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Capabilities of PR professionals for key activities lag: Asia-Pacific study shows theory and practice gaps

Abstract: A number of studies of the knowledge, skills and abilities (KSAs), competencies and capabilities of public relations and communication professionals have been carried out in the USA, UK and other countries. However, most have not engaged to any significant extent with literature in the human resource development field which specializes in defining and developing these characteristics. Also, few studies to date have related the KSAs, competencies and capabilities of practitioners to the key activities of public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 34 publications
(43 reference statements)
1
56
0
7
Order By: Relevance
“…A key aspect underpinning dialogic communication is the provision of useful content of interest to the public [ 26 , 37 ]. Other studies have confirmed the importance of this [ 4 , 19 ]. For example, Men et al [ 4 ] confirmed that leading CEOs generated engagement with the public in the form of likes, shares, and comments on Facebook by providing useful information.…”
Section: Development Of a Conceptual Framework For Analyzing Factors supporting
confidence: 60%
See 2 more Smart Citations
“…A key aspect underpinning dialogic communication is the provision of useful content of interest to the public [ 26 , 37 ]. Other studies have confirmed the importance of this [ 4 , 19 ]. For example, Men et al [ 4 ] confirmed that leading CEOs generated engagement with the public in the form of likes, shares, and comments on Facebook by providing useful information.…”
Section: Development Of a Conceptual Framework For Analyzing Factors supporting
confidence: 60%
“…For example, Men et al [ 4 ] confirmed that leading CEOs generated engagement with the public in the form of likes, shares, and comments on Facebook by providing useful information. MacNamara et al [ 19 ] also found that variables that are viewed as most relevant to identifying SMIs are the relevance of discussed topics and the quality of online content.…”
Section: Development Of a Conceptual Framework For Analyzing Factors mentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies in several countries have confirmed that communication experts understand and acknowledge these challenges. Practitioners across Europe and Asia-Pacific rate strategy communication as an important contribution to organizational success (Macnamara et al , 2017, p. 84; Zerfass et al , 2017, p. 94). However, apart from the lack of a definition, surprisingly little is known about its status quo in the professional field.…”
Section: Introductionmentioning
confidence: 99%
“…The breadth and depth of information available on the Internet and the velocity with which new data is generated is resulting in newfound challenges. Macnamara, Zerfass, Adi, and Lwin (2018) concluded that despite the paramount importance attached to digital platforms and social media, PR practitioners have low to moderate capabilities in new media usage.…”
Section: Literature Reviewmentioning
confidence: 99%